Self-Regulation Strategies Based on Cognitive Behavioral Therapy in Reducing Academic Procrastination among University Students - Sulhan Hady (Program Studi Bimbingan dan Konseling Islam, 2026)
Academic procrastination is a common problem among university students and has negative effects on academic performance, learning consistency, and psychological well-being. This article aims to examine self-regulation strategies based on Cognitive Behavioral Therapy (CBT) in reducing academic procrastination among university students. This study employed a library research design by reviewing relevant books, journal articles, systematic reviews, and previous studies related to academic procrastination, self-regulation, self-regulated learning, CBT, and counseling interventions. The literature was analyzed thematically by identifying, classifying, and synthesizing concepts and findings related to the causes of academic procrastination and intervention strategies. The results of the literature synthesis show that academic procrastination is influenced by cognitive, emotional, motivational, and behavioral factors, such as low self-efficacy, fear of failure, perfectionism, irrational beliefs, emotional avoidance, and weak self-regulation. CBT is relevant for reducing academic procrastination because it helps students identify maladaptive thoughts, reconstruct irrational beliefs, and develop more adaptive academic behaviors. CBT-based self-regulation strategies include self-monitoring, cognitive restructuring, goal setting, task breakdown, time management, self-instruction, self-reinforcement, behavioral activation, self-management, and implementation intention. These strategies can help students improve self-control, reduce avoidance behavior, manage academic tasks more effectively, and strengthen learning autonomy. Therefore, CBT-based self-regulation strategies can be recommended as an applicable counseling approach to reduce academic procrastination among university students.